Historic cities. Issues in urban conservation. - (:unkn) unknown (My University, 2019)
The book presents a comprehensive selection of important writings on urban conservation, as distinct from both heritage conservation and urban planning. There are more than sixty-five texts, ranging from early polemics by Victor Hugo and John Ruskin to a generous selection of recent scholarship, covering North America, Europe, India, China, Japan, Africa, and the Islamic world.
Keywords: Historische Stadt; Städtebaulicher Denkmalschutz; Stadterhaltung; Stadtplanung; Stadterneuerung; Stadtkultur; Stadtgrundriss; Bebauungsstruktur; Städtebaugeschichte; Denkmaltheorie